Comparison of Constitutional Requirements for Heads of State in Indonesia, the United States, and the United Kingdom Between the Principles of Non-Discrimination and People's Sovereignty - Muhammad Andrean Eka Syaputra; Herlita Eryke (PALAR | PAKUAN LAW REVIEW, 2026)
This study compares the constitutional requirements for heads of state in Indonesia, the United States, and the United Kingdom, focusing on the dilemma between the principles of non-discrimination and popular sovereignty. The requirements for heads of state reflect the application of the rule of law theory, which seeks to maintain legitimacy, political stability, and national integrity. Indonesia and the United States require candidates for heads of state to be natural-born citizens to guarantee exclusive loyalty, while the United Kingdom uses a parliamentary system with a monarchical head of state and head of government elected by parliament, without strict formal restrictions on citizenship. This study examines the meaning of these norms in the context of modern democracy, analyzes the potential for discrimination against naturalized citizens through the lens of international human rights instruments particularly the International Covenant on Civil and Political Rights (ICCPR), and interprets how each country harmonizes the principle of popular sovereignty with the protection of state sovereignty through normative mechanisms and leadership recruitment. The results show that these differences in regulations represent historical and sociocultural adaptations that adhere to the principles of the rule of law and constitutional democracy. The scientific contribution of this research lies in its human rights-based comparative analysis of three different constitutional systems in assessing the proportionality of citizenship requirements for head of state candidates in the era of modern democracy. Keywords: requirements for heads of state, democracy, rule of law, non-discrimination, popular sovereignty, Indonesia, United States, United Kingdom